Human gastro-intestinal organoid engineering: a state of the art - Benedetti, Giada; Fournon Berodia, Beatriz; De Coppi, Paolo; Giobbe, Giovanni Giuseppe (Frontiers in Chemical Engineering, 2023)
Gastrointestinal organ failure, from congenital or postnatally acquired pathologies, is a major cause of death across countries of all income levels. Organoids and engineered tissues have been widely investigated as tools to model organ functions and treat pathologies. In this review we aim to describe the progress in human organoid engineering applied to the gastrointestinal tract (namely esophagus, stomach, and intestine). Starting from the onset of the organoid culture technique, we illustrate genetic engineering, stem cell niche engineering, bioprinting, and microfluidics approaches used to integrate mechano-physiological parameters with human organoids. Thanks to these improvements, organoid technology allows disease modelling of patient-specific pathologies, and personalized treatment screening, also offering a cell source for autologous transplantation. We further present an overview of the advances of tissue engineering in animal systems, concerning novel materials and scaffolds to be combined with a variety of cell types to reconstitute a viable surrogate for implantation. The effort in this field sets organoids as an important tool in personalized and regenerative medicine. Their application combined with the advances in tissue engineering holds great potential for translational application.